Antidiarrhea Activity of Ethanol Extract of Rambutan Leaves (Nephelium lappaceum L.) in Capsule Form on Male Mice - Nitya Nurul Fadilah; Ali Nofriyaldi; Ayu Rahmawati; Srie Rezeki Nur Endah; Widya Nurul Aini; Vincent O. Imieje (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Diarrhea is characterized by changes in stool form to soft or liquid, with an intensity of bowel movements more than three times a day. One of the plants used as an alternative treatment for diarrhea is rambutan, particularly its leaves. Previous studies have shown that rambutan leaf extract can treat diarrhea. Objective: The purpose of this study was to determine the antidiarrhea activity of ethanol extracts of rambutan leaves containing tannins and flavonoids that inhibit intestinal motility. Methods: This study was conducted experimentally using the intestinal transit method, which measures the length of the intestine passed through a marker. The smaller the ratio between the length of the intestine and the marker, the greater the decrease in intestinal motility in the mice. Group 1: loperamide HCl at a dose of 4 mg/kg BW; Group 2:  placebo; Group 3: FI, FII, and FIII capsules at doses of 50 mg, 100 mg, and 150 mg. Results: The test results showed that Formulations 1, 2, and 3 had activities of 23.3%, 26.8%, and 32.3%, respectively. The capsule with the best results was formulation 3, at a dose of 150 mg. Compared with the positive control, the effectiveness of this capsule was 22% higher than that of loperamide. Conclusion: The results of this study showed that rambutan leaves extracted in capsule form effectively treats diarrhea. The one-way ANOVA test showed a significant difference between the FI, FII, and FIII groups (p <0.05).